A Small Wooden House - Tkacheva, Marina (project baikal, 2015)
The existence of the 130 Quarter is viewed in the light of the tendencies and processes of the city life. The multifunctionality and architectural image of the territory serve as the basis for its attractiveness. These features are opposed to possible quality loss. The conditions for preservation of the architectural look of the Quarter are also reviewed.
Keywords: 130 Quarter; architectural design; town-planning principles; greening; multifunctionality; advertising; illegal construction; comfort of the environment